Atividade de novo composto inseticida (dinotefuram + lambda-cialotrina) no controle do percevejo-marrom, Euschistus heros (Fabricius), na cultura da soja, Glycine max (Merrill). - Peccinelli, Murillo Cardi [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The soybean is currently the main oilseed cultivated and traded in the word. Given the magnitude of this crop and the dynamics of pests that affect the crop, new phytosanitary challenges need to be faced and clarified, aiming at the sustainability of the system and the high yields. Currently, the complex of insect-pests incidente on the soybean crop is large, causing damage and loss of productivity. The neotropical brown stink bug, Euschistus heros, is the main pest of soybean crops in Brazil. It is a species adapted to regions with high temperatures. The control with the of Chemical insecticides is still the main tool in pest management. A new insecticide compound, with a favorable toxicological profile (dinotefuram + lambdacyhalothrin) was developed with the objective of improving and increasing the management options for pests in soybean cultivation. Thus, the present work aims to evaluate the activity of the insecticide compound applied foliar pathway in the control of the brown stink bug in comparison with the main insecticides already used in the culture. The work was carried out in the city of Selvíria - MS from January 25th to March 7, 2021. The design adopted was randomized blocks (DBC), with six treatments and four replications, where each experimental plot has 90 m². The treatments were: dinotefuram + lambda-cyhalothrin at a dose of 42 + 24 g of the active ingredient (a.i.) ha-1 , thiamethoxam + lambda-cyhalothrin at a dose of 32.3 + 26.5 g of a.i. ha-1 , imidacloprid + bifenthrin at dose of 100 + 20 g a.i. ha-1 , imidacloprid + betacyfluthrin at a dose of 100 + 12.5 g a.i. ha-1 , acetamiprid + bifenthrin at a dose of 30 + 30 g a.i. ha-1 and non-applied control. Two applications were performed foliar pathway carried out with an interval of 7 days between each spraying, using a costal sprayer propelled by compressed CO2, equipped with a bar containing six tips (conejet, TXVK 8), spaced 0.5m apart, with a working pressure of 40 psi, with volume of syrup established at 150 L ha-1 . The evaluations were performed at 1, 3 and 7 days after the first application and 1, 3, 7, 10 and 15 days after the second application, bedbugs (nymphs and adults) were counted in four beats in rags per plot. Also were carried the phytotoxicity evaluations out at 1 and 3 days after each application and, at the endo f the crop cycle, yield evaluation was carried out, obtaining the weight of hrains in 5 m2 and the weight of 1000 grains by experimental plot. The data were submitted to analysis of variance by applying the F test and the averages were compared by the Tukey test (5%). It is concluded that the insecticide lambda-cyhalothrin + dinotefuram (4.8% + 8.4%) at a dose of 500 ml of pc/ha, was effective in controlling the neotropical brown stink bug, Euschistus heros, providing satisfactory control up to 15 days after second application, constituting a new option for the control of this pest in the soybean culture.

A soja atualmente é a principal oleaginosa cultivada e comercializada no mundo. Diante da grandeza desse cultivo e a dinâmica de pragas incidentes na cultura, os novos desafios fitossanitários necessitam ser abordados e esclarecidos, visando a sustentabilidade do sistema e as altas produtividades. Atualmente, o complexo de insetos-pragas incidentes sobre a cultura da soja é grande, proporcionando danos e perdas na produtividade. O percevejo-marrom, Euschistus heros, é a principal praga dos cultivos de soja no Brasil. Trata-se de uma espécie adaptada a regiões com temperaturas elevadas. O controle com o uso de inseticidas químicos consiste ainda na principal ferramenta no manejo de pragas. Um novo composto inseticida, de perfil toxicológico favorável (dinotefuram + lambda-cialotrina) foi desenvolvido com o objetivo de aperfeiçoar e aumentar as opções de manejo de pragas no cultivo da soja. Assim, o presente trabalho tem por objetivo avaliar a atividade do composto inseticida aplicado via foliar no controle do percevejo-marrom em comparação com os principais inseticidas já utilizados na cultura. O trabalho foi realizado no município de Selvíria – MS no período de 25 de janeiro a 7 março de 2021. O delineamento adotado foi de blocos casualizados (DBC), com seis tratamentos e quatro repetições, onde cada parcela experimental constou de 90 m². Os tratamentos foram: dinotefuram + lambda-cialotrina na dose de 42 + 24 g do ingrediente ativo (i.a.) ha-1, tiametoxam + lambda-cialotrina na dose de 32,3 + 26,5 g do i.a. ha-1, imidacloprido + bifentrina na dose de 100 + 20 g do i.a. ha-1, imidacloprido + beta-ciflutrina na dose de 100 + 12,5 g do i.a. ha-1, acetamiprido + bifentrina na dose de 30 + 30 g do i.a. ha-1 e testemunha não aplicada. Foram realizadas duas aplicações via pulverização foliar com intervalo de 7 dias entre cada pulverização, utilizando um pulverizador costal propelido por CO2 comprimido, equipado com barra contendo seis pontas (conejet, TXVK 8), espaçadas em 0.5m, com pressão de trabalho de 40 psi, com volume de calda estabelecido em 150 L ha-1. As avaliações foram realizadas aos 1, 3 e 7 dias após a primeira aplicação e 1, 3, 7, 10 e 15 dias após a segunda aplicação, contando-se os percevejos (ninfas e adultos) em quatro batidas no pano por parcela. Também foram realizadas avalições de fitotoxicidade aos 1 e 3 dias após cada aplicação e, ao termino do ciclo da cultura, foi realizada avaliação de produtividade, se obtendo por parcela experimental o peso de grãos em 5 m2 e o peso de 1000 grãos. Os dados obtidos foram submetidos à análise de variância aplicando-se o teste F e as médias foram comparadas pelo teste de Tukey (5%). Conclui-se que o inseticida lambda-cialotrina + dinotefuram (4,8% + 8,4%) na dose de 500 ml do p.c./ha, foi eficiente no controle do percevejo-marrom, Euschistus heros, proporcionando controle satisfatório até 15 dias após segunda aplicação, constituindo-se como nova opção para o controle da referida praga na cultura da soja.
Activity of a new insecticide compound (dinotefuram + lambda-cyhalothrin) on control of neotropical brown stink bug, Euschistus heros (Fabricius), in soybean crop, Glycine max (Merrill).
Keywords: Integrated pest management; Glycine max; Pentatomidae; Manejo integrado de pragas